Peraturan Presiden Nomor 54 Tahun 2010 tentang Pengadaan Barang/Jasa Pemerintah - [Tidak Terdaftar] (Pustaka Yustisia, 2010)
Peraturan Presiden No. 54 Th. 2010 tentang Pengadaan Barang/Jasa Pemerintah